'Ink Art' as strategy for Hong Kong institutions. Issue 1 (2nd January 2017) - Vigneron, Frank
Abstract: In both their wider cultural dimensions and the institutional practices they stem from, the practices of ink art in Hong Kong manifest themselves in a variety of discourses ranging from the 'traditionalism' of the conservative nativists to the 'contemporaneity' of artists and institutions often identified as being closer to 'Western' culture. Even though the most influential discourse about ink art in Hong Kong has clearly been produced by official institutions, like the future museum of visual culture called M+ and the already existing Museum of Art, it has also been profoundly influenced by private associations whose influence has been far reaching. The most visible of these private associations in Hong Kong is the Ink Society, whose founding members and their affiliates and friends have played a central role in the early debate about the nature of ink art in the history of local arts. Through an analysis of a failed attempt by the Ink Society to bid for the right to manage a historical site, this paper attempts to unravel some of the ideas that support the notion of ink art in Hong Kong.